Reportaż radiowy – definicja i podział - Klimczak, Kinga (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article presents Polish radio documentaries. The present author discusses a scholarly definition and the genre-specific characteristics of a documentary. This paper also offers its description, based on interviews with a few Polish feature makers.